Pengaruh kualitas pelayanan terhadap kepuasan nasabah pada Bank Nagari cabang Muaralabuh - Chintia Monica; Doni Marlius (JURNAL PUNDI, 2023)
This research was conducted at the Muaralabuh branch of the Nagari Bank. The aim is to determine the effect of service quality on customer satisfaction at the Bank Nagari Muaralabuh branch. This study uss quantitative methods.the population is the customer of the Muaralabuh branch of the Nagari Bank as many 100 respondents. The sampling technique used was using the slovin formula so that the sample in this study was 100 respondents. Data analysis using multiple linear regression analysis assisted by the computer program SPSS 20 for windows. The results of this study indicate that service quality has a positive and significant effect on cutomer satisfaction at the Muaralabuh branch of Nagari Bank.Keywords: service quality, customer satisfaction